Undiagnosed connective tissue diseases: High prevalence in pulmonary arterial hypertension patients. Issue 39 (September 2016) - Cavagna, Lorenzo; Codullo, Veronica; Ghio, Stefano; Scirè, Carlo Alberto; Guzzafame, Eleonora; Scelsi, Laura; Rossi, Silvia; Montecucco, Carlomaurizio; Caporali, Roberto
Abstract : Abstract: Among different subgroups of pulmonary arterial hypertension (PAH), those associated with connective tissue diseases (CTDs) have distinct hemodynamic and prognostic features; a correct etiologic diagnosis is thus mandatory. To estimate frequency and prognosis of previously undiagnosed CTDs in a suspect idiopathic (i) PAH cohort. Consecutive patients with PAH confirmed by right heart catheterization referred at the Cardiology Division of our Hospital without a previous rheumatological assessment or the occurrence of other conditions explaining PAH were checked for CTD by a clinical, laboratory, and instrumental evaluation. Survival in each group has also been analyzed. In our study 17 of 49 patients were classified as CTD-PAH, corresponding to a prevalence (95% CI) of 34.7% (21.7–49.6%). ANA positivity had 94% (71.3–99.9%) sensitivity and 78.1% (60–90.7%) specificity for a diagnosis of CTD-PAH; Raynaud phenomenon (RP) showed 83.3% (51.6–97.9%) sensitivity and 100% (90.5–100%) specificity for the diagnosis of Systemic Sclerosis (SSc)-PAH. At diagnosis, SSc patients were older and had a lower creatinine clearance compared with iPAH and other CTD-PAH. After a median follow-up of 44 (2–132) months, 18 of 49 (36.7%) patients died: 31.2% in the iPAH group, 20% in the CTD-, and 58.3% in the SSc-PAH group. Mortality was significantly higher in SSc-PAH (HR 3.32, 1.11–9.95, P <0.05) versus iPAH. We show a high prevalence of undiagnosed CTDs in patients with iPAH without a previous rheumatological assessment. All patients with RP were diagnosed with SSc. Our data stress the importance of a rheumatological assessment in PAH, especially because of the unfavorable prognostic impact of an associated SSc.